Enhancing VANET Connectivity through AODV-Assisted PMIPv6: A Behavioral and Technical Evaluation - Hussain, Haider N.; AL-Hashmy, Hisham Noori (Informatica, 2025)
This paper presents a hybrid framework that combines the Ad hoc On-Demand Distance Vector (AODV) routing protocol with Proxy Mobile IPv6 (PMIPv6) to improve internet continuity and routing resilience in Vehicular Ad Hoc Networks (VANETs). In addition to technical integration, the framework introduces a behavioral perspective by modeling how vehicular nodes develop network adaptability awareness (NAA) and engage in voluntary protocol optimization behavior (VPOB). The proposed model is evaluated through simulations involving an initial set of 562 vehicular nodes, from which 478 complete datasets were retained after preprocessing. Experimental results indicate that the hybrid framework achieves up to a 42% improvement in handover continuity and a 35% reduction in packet loss when compared with conventional MIPv6 and proposed MIPv6 extensions. PLS-SEM results indicate that vehicular node participation, protocol performance, and configuration training positively affect NAA, which subsequently predicts VPOB. This supports the adoption of locally implemented (PMIPv6) adaptable, behavior-aware protocols to strengthen VANET communication resilience under mobility and congestion stress.